onnonal assay in repeat breeding cows and buffaloes - VENKATESAN, P S; SHANKAR, M SHYAM; SUBRAMANIAN, A (The Indian Journal of Animal Reproduction, 2005)
A study was conducted to assess the hormonal status in 70 repeat breeder and 14 regular breeder cows and buffaloes inChennai, Tamilnadu. Circulating progesterone level was higher on day 0 and lower on day 7 in repeat breeder than in regular breeder.Estrogen level was lower on day 0 and day 7 in repeat breeder than regular breeder cows and buffaloes. Regular breeder cows had asignificant higher level of T3 and T4 on day 0 than the repeat breeder cows and buffaloes. It is concluded from the study that thisdifference in hormonal concentration of repeat breeders from regular breeders might be resJfnsible for the reproductive disorders incows and buffaloes.
Keywords: Estrogen; thyroid hormones; progesterone; repeat breeder